Statistical Features of Polar Cap North and South Indices in Response to Interplanetary and Terrestrial Conditions: A Revisit - Jong‐Sun Park; Quan Qi Shi; Oleg A. Troshichev; Khan‐Hyuk Kim; Jih‐Hong Shue; Timo Pitkänen; Hui Zhang (Space Weather)
Abstract In this study, we investigate statistical features of polar cap north (PCN) and south (PCS) indices in response to various interplanetary conditions (interplanetary magnetic field [IMF] orientation in three‐dimensions) and terrestrial conditions (seasonal and magnetic local time [MLT] locations of the index stations). The concurrent PCN‐PCS pairs for 1998–2002 and 2004–2018 are divided based on their sign type (positive‐positive, negative‐negative, negative‐positive, and positive‐negative PCN‐PCS pairs) and time coverage (the times when both index stations are in the dawn/dusk MLT sector during northern summer/winter). Analyzing the IMF orientation dependence on the occurrence probabilities of concurrent indices and on the differences between the indices in various sign types for each time coverage reveals that the statistical features in PCN‐PCS pairs obtained in the dawn MLT sector can be largely explained by the effects of the three‐component IMF (related to the polar cap convection patterns) combined with season (related to the hemispheric asymmetry in solar illumination‐induced ionospheric conductance). However, those obtained in the dusk MLT sector are controlled dominantly by seasonal effects rather than IMF orientation effects. Our findings indicate that PCN‐PCS pair data provide local views about the solar wind‐magnetosphere‐ionosphere (SW‐M‐I) coupling system with different control efficiencies of IMF orientation and season depending on the MLT location of the stations. Therefore, introducing polar cap indices recorded simultaneously at various locations in both hemispheres and analyzing them are strongly required to infer global views of the coupled SW‐M‐I system in the open field regions with higher confidence.